THE HISTORICAL OF GROWTH ENGLISH FOR SPECIFIC PURPOSE - Ernita Daulay (UIN Sumatera Utara, 2019)
This study aims to understand English for Specific Purposes (ESP): a very significant branch of ELT that includes various linguistic efforts to define it, trace its historical growth, discuss its characteristics, and try to find out its scope and purpose. Although many conflicting views have been reported in defining ESP but there seems to be an eventual agreement that it is limited to teaching English to students who have specific goals and objectives: these goals may be professional, academic or scientific. Thus it is not a special discipline that is major in ESP but the specific goals of certain students. The same thing has been reinforced by discussions related to the absolute characteristics and variables. The historical growth of ESP has also been traced and it has been reported that although considered a modern approach, ESP textbooks exist even in the sixteenth century. It was found that the purpose of the ESP course was to enable students to function adequately in the target situation. Thus the ESP program must be directed towards the goal, directed by students and directed by the situation.